International Business: Environments & Operations - John D. Daniels; Lee H. Radebaugh; Daniel Sullivan (United Kingdom Pearson, 2022)
Balancing authoritative theory and meaningful practice, International Business: Environments and Operations engages students on the subject of conducting business in international markets. The authors' descriptions and ideas of international business are enhanced with contemporary examples, scenarios, and cases that help students effectively apply what they've learned. Now in its 17th Edition, International Business remains one of the best-selling and most authoritative international business texts available. As rigorous and practical as ever, this edition remains current through updated author-written cases and expanded coverage of relevant political, economic, social, and institutional changes.
Keywords: Business; Textbooks; International Business and Management (ECO2023-N )